12. ESTABLISHING AND EVALUATING HEMATOLOGICAL PARAMETER REFERENCE INTERVALS FOR ADULTS AT THE HEMATOLOGY- BLOOD TRANSFUSION DEPARTMENT OF LE VAN THINH HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2024)
Objective: Establising and evaluating reference intervals for hematological parameters in adults at Le Van Thinh Hospital for examination and testing.Subject and method: A cross-sectional descriptive study was conducted from January 2023 to December 2023 involving 2368 individuals aged 18-28 (1179 males, 1189 females) who participated in health examinations and hematological testing at the Hematology- Blood Transfusion Department of Le Van Thinh Hospital. The results were analyzed using SPSS 20.0 software, calculating the mean values and standard deviations for normally distributed variables. Gender differences were compared using a t-test (for comparing means) with a significance level of p
Keywords: Reference interval, hematology, healthy adult